Pengembangan Program Pembelajaran Keterampilan Vokasional Membuat Buket Bunga Bagi Anak Tunagrahita Ringan - Hendri Abdul Qohar (Journal on Education, 2023)
Mild mentally retarded children generally experience academic learning difficulties, because of that the learning program for them is more directed at mastering vocational skills, so that children have the provision to live in society and every year competition activities are always there, one of them is a flower bouquet making contest. This study aims to obtain an overview of the development of a vocational skill learning program for making flower bouquets. This research uses a qualitative approach with descriptive methods. Data collection techniques used are observation, interviews, documentation studies, FGD, and validation. The results of the study show that children with mild mental retardation have the basic ability to make flower bouquets. In the implementation of learning vocational skills to make a bouquet of flowers the teacher makes plans, carries out learning activities, and evaluates. The current form of the program, the meeting is only 1 time with the duration of the students' boring time and the material is less in-depth. The forms of programs in Kembangan are indicators, objectives, materials, media and evaluation. This research is recommended to teachers to be a reference in carrying out learning in the classroom.